Let Us Create a Physical IoT Device Using AWS and ESP Module - Sudip Chakraborty; P. S. Aithal (International Journal of Management, Technology and Social Sciences (IJMTS), 2023)
Purpose: This research paper explores the feasibility of creating a physical AWS IoT device using an ESP module. The paper describes the steps and process of building such a device, including the required hardware and software components. The ESP module is chosen for its low cost, small size, and ability to connect to the internet through Wi-Fi. The AWS IoT platform manages and monitors the device, including the ability to receive and send data to and from the device. The paper includes a detailed explanation of the programming and setup involved in creating the device and the challenges and limitations encountered during the process. Ultimately, this paper demonstrates that creating a physical AWS IoT device using an ESP module is possible, providing a cost-effective solution for developers looking to build IoT devices. The project code is available to download. Design/Methodology/Approach: Initially, we create things inside the AWS cloud. Download all certificates and credentials. Then the downloaded credential, we added to the project variable—the Code compiles and runs. Our ESP8266 hardware is then ready to receive the topic. We use two channels to send the topic to our ESP Module. We can send topics using the AWS cloud MQTT test client interface. Another way is from the C# dot net MQTT client application. We develop an application in the visual studio that can update the AWS device shadows. We will notice that data sending to the AWS Device shadows and updating the ESP module almost in real-time. Findings/Result: We use the ESP module to experiment with the AWS IoT interface. Sometimes researchers need to transfer the data over IoT. So here we provide the complete practical guide for IoT experiments. Here we demonstrate How to create the IoT devices and send/update the IoT Devices’ Shadow. We integrated the C# MQTT client. Using our created application, we will update AWS cloud MQTT devices shadows. It might be more help full for new researchers to integrate IoT into their projects. Originality/Value: After studying Several documents, we created this paper after doing lots of experiments so that our researcher could experiment easily. The available Code is wholly tested and workable. Our researchers can integrate it into their projects with a little customizing effort. The researcher can find some revenant documents for their research work. Paper Type: Experimental-based Research.